(untitled) (American Journal of Islam and Society, 2016)
In 2006 the first International Congress of Islamic Civilization in Southern Africa was hosted by AwqafSA (www.awqafsa. org.za) and IRCICA (Centre for Islamic History, Art, and Culture www.ircica.org) at the University of Johannesburg. IRCICA, the prime mover and funder of this and similar conferences and congresses worldwide, has been actively promoting these platforms to bring academics, scholars, researchers, and other stakeholders together to highlight research outputs and findings that reflect upon the status and position of Muslim minorities worldwide. Since Southern African Muslim communities form an integral part of Africa’s Muslims, it decided to host a follow-up event in the region. IRCICA once again teamed up with AwqafSA, which had been in close contact with IRCICA since the 2003 Uganda “Islamic Civlization in East Africa” conference. For this congress, AwqafSA partnered with the International Peace College of South Africa (IPSA) and the University of KwaZulu- Natal (UKZN). It also teamed up with ITV, Radio Al-Ansaar, and the Minara Chamber of Commerce. Since UKZN was the main academic partner, the congress was held from March 4-6, 2016, at the Senate Chambers of UKZN’s Westville campus. The organizers’ objectives for the congress were to (a) increase people’s knowledge of the history and heritage of Southern Africa’s Muslims, (b) strengthen cooperation among Muslim and African nations and their peoples by producing and disseminating Islamic and cultural knowledge, and (c) offer a forum for the true understanding of Islamic culture in the world. Donal McCracken (acting dean of research, College of Humanities) officially welcomed the delegates. Following his opening remarks, the audience heard from the representatives of the Congress Organizing Committee. Zeinoul Cajee (CEO, AwqafSA), Halit Eren (director-general, IRCICA), and Shaykh Ighsaan Taliep (IPSA). Eren underscored the importance of these ...